RISK ADJUSTMENT DETERMINATION WITH CHAIN-LADDER METHOD ON LIABILITY FOR INCURRED CLAIM (LIC) GENERAL INSURANCE BASED ON IFRS 17 - Priskilla, Felicia
Insurance companies must be able to anticipate an increase in the severity of unexpected claims to avoid insolvency. One way to anticipate this is by calculating the required risk adjustment. However, not all compensations are paid immediately after the incident occurs, allowing for the construction of a run-off triangle that contains paid claims with specific accident years and development years. This run-off triangle can be applied to the chain-ladder method to determine the required risk adjustment for general insurance companies. Claim value predictions can also be applied using two methods: the development factors (DF) method and the generalized linear model (GLM). These claim value predictions will be applied to the bootstrapping method, resulting in multiple claim values that can later be used to calculate the reserve amount. The obtained risk adjustment values are IDR 89,441,124 and IDR 95,401,801 using the DF and GLM methods, respectively. The DF method is considered to provide a better risk adjustment because its risk adjustment value is less fluctuating across various bootstrapping iterations compared to the GLM method.